Effects of hypoxic interval training on cycling performance - Roels, B.; Millet, G. P.; Marcux, C. J. L.; Coste, O.; Bentley, D. J.; Candau, R. B. (Medicine & Science in Sports & Exercise, 2005)
Purpose: The aim of this study was to test the hypothesis that intermittent hypoxic interval training improves sea level cycling performance more than equivalent training in hypoxia or normoxia.